Eksplorasi berpikir kreatif melalui discovery learning Bruner - Nu'man, Mulin (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2020)
Creative thinking is an essential component of advanced mathematical thinking. The components of creative thinking are lateral thinking (creating one's own and non-routine ways), divergent thinking (using a variety of ways), and convergent-integrative thinking (using patterns in other situations). One way to develop creative thinking is learning with Bruner's discovery learning model, namely learning with an enactive, iconic, and symbolic stage. Learning activities with Bruner's discovery learning on the material of the two-variable linear equation system (SPLDV) to explore creative thinking are: 1) preliminary activities: goals and perceptions, 2) core activities include: the enactive stage, which is giving contextual problems to be solved themselves of students to explore lateral thinking, the iconic stage, which is writing solutions and presentations to explore divergent thinking, and the symbolic stage, which is the elaboration of the results of the previous stages to be brought to the mathematical process in the form of modeling and elimination and substitution methods to explore lateral thinking, divergent thinking, and convergent thinking integrative, and 3) closing activities: feedback and conclusions.